STUDENTS STRATEGY TO SOLVE DIFFICULTIES IN ENGLISH VOCABULARY ACQUISITION - Ariyanti, Septika; Kurniati, Desi; Gustianing, Defy (Universitas Aisyah Pringsewu, 2022)
The purposes of the present study are to explore students’ difficulties in vocabulary acquisition and to discover the strategy which able to solve students difficulties in vocabulary acquisition. Strategies are specific methods used to approaching a problem or task, modes of operation for achieving a particular end, plan or designs for controlling and manipulating certain information. The research object of this study is the students in seventh A of SMP Negeri 7 Metro. The researchers use observation, interview and document to collect the data. The result of the study shows that there are some strategy to solve the students difficulties in English vocabulary acquisition: meta-cognitive strategy, cognitive strategy, and socio-affective strategy. Each of strategies plays important roles in vocabulary acquisition.